Tootsie [videorecording (DVD)] - Pollack, Sydney, 1934-2008; Hoffman, Dustin, 1937-; Lange, Jessica; Garr, Teri, 1944-; Coleman, Dabney, 1932-; Davis, Geena (Criterion collection, 2014)
Follows the increasingly elaborate deception of a down-on-his-luck New York actor who disguises himself as a woman to get a coveted soap opera gig; while his female persona skyrockets to fame, he finds himself learning to be a better man.